Blurring boundaries: an analysis of the digital platforms-military nexus - Andrea Coveri; Claudio Cozza; Dario Guarascio (Global Labor Organization (GLO), 2023)
This work analyzes the mutual dependence linking digital platforms, i.e., 'Big Tech', and the military apparatus. Three main elements are at the roots of such dependence: an 'originary linkage' binding the development of digital platforms with governments' R&D military efforts, the critical nature of infrastructures and technologies controlled by platforms, and their role as their government's 'eyes and ears' (both at home and abroad). Focusing on the US, we first document the growing relevance of these corporations as Department of Defence contractors. Second, we explore a selection of multi-year contracts entrusting platforms to develop and manage critical technologies and infrastructures for military purposes. Finally, we document the direct involvement of major US-based platforms in war scenarios.
Keywords: L12; L22; P12; 330; monopoly capital; imperialism; war; nation-states; digital platforms; military industry